Developing Strategy for Young Da'i: Da'wah Education at the Nadhatul Ulum Islamic Boarding School - Azka, Ibnu Azka; Nurhalisa, Siti; Baldan Haramain, Fathur (IJIBS, 2024)
Islamic boarding schools in Indonesia play a strategic role in character-building and spreading Islamic teachings. One key element is the role of the dai or preacher in conveying Islamic values to students and the surrounding community. However, the development of preaching in these schools faces several challenges, affecting its quality and impact. This research explores how Islamic boarding schools and preachers can design more effective development strategies aligned with contemporary demands to improve the quality of preaching and the schools' contribution to forming an Islamic values-based society. The study focuses on the education of Dakwah Pembina at the Nahdlatul Ulum Islamic Boarding School in Soreang Maros, addressing three main questions: the implementation of the Guidance Da'wah Strategy, the materials used to support da'wah training for students, and the advantages and disadvantages of Santri da'wah training at the school. The research aims to deeply understand the Da'wah Strategy of Guidance at Nahdlatul Ulum, explore supporting materials for Da'wah training, and analyze the training's strengths and weaknesses. A qualitative approach is used, with data collected through observation, interviews, and documentation. Results show that Nahdlatul Ulum Soreang Maros implements the Guidance Da'wah Strategy through various activities. Supporting materials include Formal Madrasah Education and the Study of the Yellow Book. The advantages of Santri da'wah training include providing knowledge, while the disadvantages are the need for teacher creativity and attention in implementing da'wah training.